The Phenomenon of Cognitive Overload in Digital Learning: A Review of Instructional Design Strategies (Literature Study) - Yudi Hendrilia; Erna Yantiningsih; Mumu Muzayyin Maq; Nana Citrawati Lestari; Dwi Hadita Ayu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid integration of technology in education often triggers the phenomenon of cognitive overload, which hinders the effectiveness of information processing among learners. This study aims to conduct an in-depth analysis of various instructional design strategies that can mitigate cognitive load in digital learning environments through a systematic literature review approach. Data were collected from reputable academic databases, focusing on literature that connects multimedia design variables and cognitive psychology over the past ten years. The results of the analysis indicate that the mitigation of extraneous cognitive load can be effectively achieved through the application of segmentation, signaling, and modality principles. The findings highlight that instructional designs which break information into smaller units, provide clear visual cues, and balance visual auditory channels significantly improve information retention and working memory efficiency. In addition, the study reveals the presence of the expertise reversal effect, which requires instructional design to be adaptive to learners’ prior knowledge. In conclusion, this study offers strategic recommendations for instructional media developers to prioritize human cognitive architecture over technological aesthetics in order to create more effective and cognitively friendly digital learning ecosystems.